Các nguyên tắc xây dựng pháp luật - Hảo, Võ Trí (VNU Journal of Science: Legal Studies; Vol 20 No 1, 2004)
The author has analyzed the role of correct principles in building law. Then emphasise three principle: democratic, balancing and resoluting conflict interests, impartial. The author analyzed: - The reasons why we should support these principle in buiding the rule of law; - Imperfect points in implementing these principle; - Measures to correct these imperfect points.